A Review on Impact of Training Program on Knowledge and Practice Regarding Hypertension among Accredited Social Health Activist - O, Shalini; Solomon, Smriti G. (International Journal of Nursing and Medical Investigation, 2024)
Hypertension (HTN) is the term used to describe high blood pressure (BP). One of the major causes of morbidity and mortality and a public health issue that affects all nations in the world is HTN. The low diagnosis of HTN in rural India is caused by a number of obstacles. Accredited Social Health Activist (ASHA) workers who work for mother and child health programs across the nation could be used to improve HTN control because rural India has low access to healthcare services. ASHAs can receive training to facilitate community-based group discussions focused on education and to assist people in controlling high BP. ASHAs may obtain training to support people and lead community-based group discussions on high BP management. Following the intervention, the ASHAs had a greater understanding of and use for HTN. According to the ASHAs, the training materials were easy to understand and effective at educating local populations. This study proved that health education provided by community health practitioners improved the adherence of HTN patients to low-sodium diets and medications. More health issues than any other condition are caused by HTN globally. Rural communities have lower levels of awareness of available HTN control options. We came to the conclusion after examining the available literature that training programs could improve the understanding and attitude of ASHA employees about HTN.